Inducible Activation of FGFR2 in Adult Mice Promotes Bone Formation After Bone Marrow Ablation. (12th September 2017) - Xu, Wei; Luo, Fengtao; Wang, Quan; Tan, Qiaoyan; Huang, Junlan; Zhou, Siru; Wang, Zuqiang; Sun, Xianding; Kuang, Liang; Jin, Min; Su, Nan; Jiang, Wanling; et al.
ABSTRACT: Apert syndrome is one of the most severe craniosynostoses, resulting from gain‐of‐function mutations in fibroblast growth factor receptor 2 (FGFR2). Previous studies have shown that gain‐of‐function mutations of FGFR2 (S252W or P253R) cause skull malformation of human Apert syndrome by affecting both chondrogenesis and osteogenesis, underscoring the key role of FGFR2 in bone development. However, the effects of FGFR2 on bone formation at the adult stage have not been fully investigated. To investigate the role of FGFR2 in bone formation, we generated mice with tamoxifen‐inducible expression of mutant FGFR2 (P253R) at the adult stage. Mechanical bone marrow ablation (BMX) was performed in both wild‐type and Fgfr2 mutant (MT) mice. Changes in newly formed trabecular bone were assessed by micro‐computed tomography and bone histomorphometry. We found that MT mice exhibited increased trabecular bone formation and decreased bone resorption after BMX accompanied with a remarkable increase in bone marrow stromal cell recruitment and proliferation, osteoblast proliferation and differentiation, and enhanced Wnt/β‐catenin activity. Furthermore, pharmacologically inhibiting Wnt/β‐catenin signaling can partially reverse the increased trabecular bone formation and decreased bone resorption in MT mice after BMX. Our data demonstrate that gain‐of‐function mutation in FGFR2 exerts a Wnt/β‐catenin‐dependent anabolic effect on trabecular bone by promoting bone formation and inhibiting bone resorption at the adult stage. © 2017 American Society for Bone and Mineral Research.